2008
DOI: 10.1007/s10646-008-0234-9
|View full text |Cite
|
Sign up to set email alerts
|

Ecological risk of methylmercury in Everglades National Park, Florida, USA

Abstract: Dramatic declines in mercury levels have been reported in Everglades biota in recent years. Yet, methylmercury (MeHg) hot spots remain. This paper summarizes a risk assessment of MeHg exposure to three piscivorous wildlife species (bald eagle, Haliaeetus leucocephalus; wood stork, Mycteria americana; and great egret, Ardea albus) foraging at a MeHg hot spot in northern Everglades National Park (ENP). Available data consisted of literature-derived life history parameters and tissue concentrations measured in 60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…Ecological risk assessments have indicated that populations of top predators such as wading birds could be adversely affected by MeHg contamination (Duvall and Barron, 2000). MeHg levels in top predator fish in ENP are among the highest levels in the nation for freshwater fish (Axelrad et al, 2009), and represent a threat to fish-eating avian and mammalian wildlife (Rumbold et al, 2008). Total mercury concentrations and spatial patterns in soil and water in the Everglades do not explain the bioaccumulation and distribution of mercury in prey fish; therefore other biogeochemical factors must be at play Stober et al, 2001).…”
Section: Impacts On Mehg Production and Bioaccumulationmentioning
confidence: 99%
“…Ecological risk assessments have indicated that populations of top predators such as wading birds could be adversely affected by MeHg contamination (Duvall and Barron, 2000). MeHg levels in top predator fish in ENP are among the highest levels in the nation for freshwater fish (Axelrad et al, 2009), and represent a threat to fish-eating avian and mammalian wildlife (Rumbold et al, 2008). Total mercury concentrations and spatial patterns in soil and water in the Everglades do not explain the bioaccumulation and distribution of mercury in prey fish; therefore other biogeochemical factors must be at play Stober et al, 2001).…”
Section: Impacts On Mehg Production and Bioaccumulationmentioning
confidence: 99%
“…In this regard, several authors have reported the highest concentration of polychlorinated biphenyls and chlorinated pesticides in Lepisosteus oculatus and A. tropicus compared to other fish inhabiting the same water bodies (Carvalho et al 2009). In the same way, an elevated concentration of metals have been registered in L. platyrhincus and L. osseus (Rumbold et al 2008), as well as very high concentrations of polycyclic aromatic hydrocarbons (PAHs) in L. oculatus (Luna et al 2005). The physiological effects reported for these pollutants include liver lesions characterized by the accumulation of melanomacrophage centers, pancreatitis and perivascular cuffing (Hartley et al 1996), esterases inhibition (Huang et al 1997) and the reduction in 17 b-estradiol levels (Orlando et al 2002).…”
Section: Introductionmentioning
confidence: 95%
“…The corresponding LOAEL values were based on concentrations in plasma, liver, brain, and kidney, and are presented in Table 2 . Using an average bm of 1.0 kg for great egret reported by Rumbold et al ( 2008 ) , and a rate of intake of food of 0.181 kg/day estimated from an allometric equation for wading birds (Kushlan 1978 ;US EPA 1993 ) , the dietary LOAEL was calculated to be 0.091 m g MeHg/g (bm)/day.…”
Section: Review Of Mehg Toxicity To Birdsmentioning
confidence: 99%